Intra-Organizational Bargaining: Wage Differentials Among Saskatchewan Schoolteachers - Ohtsu, Makoto; Verma, Anil (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper attempts to determine the extent to which the concept of «intra-organizational bargaining», suggested by Walton and McKersie, among others, is useful in analyzing wage differentials between sub-groups within a local union. Based on historical data for public schoolteachers in Saskatchewan, the results show that the relative power of sub-groups within the union has a much stronger bearing on internal wage differentials than do the economic variables. This lends strong support to the intraorganizational bargaining model of internal wage differentials.